DESIGN OF HERIC INVERTER FOR PHOTOVOLTAIC SYSTEM - P N, Vikash; K. , Balachander (International Journal of Psychosocial Rehabilitation, 2020)
Introduction:. The Highly Efficient and Reliable Inverter Concept (HERIC) [6] inverter is a cost-effective topology that has low leakage currents [4] and a relatively high efficiency. Thus, it is very suitable for transformerless PV systems with boost converters. Due to the reduced number of switches, switching losses may be reduced. However, with the modulation methods, it is difficult to simultaneously maintain the high efficiency, reduced switching losses, good power quality, and reactive power [10] injection of the HERIC inverter. In this project, a hybrid sine pulse width modulation (H-SPWM) scheme is thus proposed to achieve those performances. The hybrid scheme adopts the conventional SPWM [7] in the case of generating the positive power. When generating the negative power, a modulation scheme, which only requires the operation of freewheeling switches, is specifically proposed. The results demonstrate that the proposed hybrid SPWM method achieves a better performance in terms of reactive power injection than the conventional UP-PWM scheme [9] and a higher efficiency than the PWM with dead time. In addition, the proposed H-SPWM [12] scheme also enables better power quality and achieves better performance and improves the THD more than existing methods.